(untitled) (Journal of European Studies (JES), 2018)
The English and French literatures interact intimately with each other as, for instance, those of Iran and South West Asia. In particular, the 19th century formed the heyday of both the British and French empires, which spread over large regions of the world. Increased travel and communication between England and France, apart from the great increase in education in both countries at the time, enabled writers in England to borrow from the flowering of new approaches to poetry in France that encouraged a fusion of art and literature, spearheaded by a literary movement named the Parnassians. The article pinpoints significant Parnassian writers and their work on both sides of the English Channel.